2018
DOI: 10.22159/ajpcr.2018.v11i10.24993
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Moringa Tea Against Cypermethrin-Induced Hepatorenal Dysfunction, Oxidative Stress, and Histopathological Alterations in Female Rats

Abstract: Objectives: Exposure to α-cypermethrin (α-CP) may yield reactive oxygen species (ROS) that is responsible for oxidative stress in mammals. A variety of antioxidants were used to alleviate α-CP-induced toxicity in experimental animals. To the best of our knowledge, there are no attempts of using Moringa oleifera L. (MO) plant extracts against α-CP-induced toxicity. Therefore, this study was conducted.Methods: A total of 16 adult female rats were segregated into equally four groups: One group administered α-CP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…In the present investigation decreased mortality may be due to boosting up scavenging activity of free radicals by Moringa oleifera. Administration of MLE restored the activities of AST, ALT, ALP, LDH, GGT and total protein toward the normal level induced by pesticides as shown by many workers [26,51,52]. The reversal of increased transaminases by MLE supplement may be due to the healing of hepatic parenchyma and regeneration of hepatocytes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present investigation decreased mortality may be due to boosting up scavenging activity of free radicals by Moringa oleifera. Administration of MLE restored the activities of AST, ALT, ALP, LDH, GGT and total protein toward the normal level induced by pesticides as shown by many workers [26,51,52]. The reversal of increased transaminases by MLE supplement may be due to the healing of hepatic parenchyma and regeneration of hepatocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Khalil and Korni (2017) have also been reported that Moringa oleifera leaves extract helps in boosting growth, immune system by mitigate oxidative stress in fishes [24]. Previous studies reported the attenuating effect of Moringa leaf extract against pesticides in rats and fishes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Dalam kondisi seperti ini, beban kerja tubuh menjadi semakin berat yang membuat sistem imun tubuh menurun dan menyebabkan peradangan. Saat terjadi peradangan tubuh akan melawan dengan mengeluarkan zat anti peradangan melalui reaksi oksidasi yang berguna namun menimbulkan dampak buruk yang berbahaya dibanding peradangan itu sendiri (Wang et al, 2017, Mansour et al, 2018.…”
Section: Pembahasanunclassified
“…They include many classes of anthropogenic chemicals such as pesticides (Castellani et al, 2021). Methomyl (Lannate1), S‐methyl N‐(methylcarbamoyloxy) thioacetimidate (C5H10N2O2S), is a carbamate insecticide used frequently for controlling insect pests on a set of field crops including fruits, vegetables, grains, and cotton in different parts of the world (Mansour et al, 2018). Methomyl is one of the most commonly used insecticides which was classified as an endocrine disrupter through World Wildlife Fund International in 1997 (Shun‐long et al, 2013).…”
Section: Introductionmentioning
confidence: 99%